Investigation of a spiro to ansa rearrangement with di-functional alcohols in cyclotriphosphazene derivatives - Besli, Serap; Coles, Simon J.; Coles, L. Susanne; Davies, David B.; Kilic, Adem (Pergamon-Elsevier Science Ltd, 2012)
A Spiro to ansa rearrangement has been investigated by the reactions of cyclotriphosphazene derivatives having five-membered Spiro rings, N3P3Cl4[O(CH2)(2)NH], (1) and N3P3Cl4[O(CH2)(2)O], (2) with disodium salts of 1,3-propanediol and 2,2,3,3-tetrafluoro-1,4-butanediol. Compounds 1 and 2 with the strong nucleophile, 1,3-propapanediol, give rearrangement reactions to form stable ansa-ansa compounds, whereas reaction of compounds 1 and 2 with the fluorinated alkoxide results in normal nucleophilic substitution at the PCl2 groups and no rearrangement takes place with the weaker nucleophile. The synthesised compounds (3a, 3b,4b, 5a-d, 6c and 6d), have been fully characterised by elemental and mass (MS) analysis, and by H-1 and P-31 NMR spectroscopy. Crystal structures of 3b, 4b, 5b-d and 6c have been characterised by X-ray crystallography. It is found that 1,3-propapanediol is a sufficiently strong nucleophile to cause a spiro to ansa rearrangement in the mono-spiro cyclotriphosphazenes compounds 1 and 2, even though crystallographic evidence shows that formation of the seven- and eight-membered ansa-ansa rings in compound 3b results in distortion and compression of the cyclophosphazene ring. A possible mechanism, which depends on attack of the anionic oxygen nucleophile at spiro-bearing phosphorus atom, was used to help understand the spiro-to-ansa rearrangement reaction. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Cyclotriphosphazenes; Molecular rearrangement; Crystal structures; N3P3 ring distortions; Mechanism